MANAJEMEN PENGELOLAAN DANA DESA SUNGAI RAMBAIKECAMATAN TEBO ULU KABUPATEN TEBO - Rio Iqlandia; M. Nazori; Mellya Embun Baining (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
This research aims to analyze the management of village fund utilization in enhancing the development of Sungai Rambai Village, Tebo Ulu Subdistrict, Tebo Regency. This study uses a qualitative method with primary data sources obtained through interviews with village officials and documentation, as well as secondary data from the village's financial reports. The results indicate that the management of village funds in Sungai Rambai Village has been carried out in accordance with the established stages of planning, implementation, and accountability. However, there are obstacles in the management of village funds, including the lack of community participation in deliberations on the planning of village fund utilization, as well as limited transparency and accountability in the open delivery of financial reports to the community. The use of the Sungai Rambai Village fund budget, Tebo Ulu Subdistrict, Tebo Regency, as seen from the financial performance of the village fund budget in 2017-2021, falls into the good category, with all annual budget expenditures realized in accordance with the planned allocations.